Kolaborasi Guru Bimbingan dan Konseling dengan Guru Pendidikan Agama Islam dalam Pembinaan Kesehatan Mental Peserta Didik di SMKN 1 Sijunjung - Meri Anjelia Sasmita; Nasrul; Hilmi; Odsisa Putera (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to describe and analyze the collaboration between Guidance and Counseling (BK) teachers and Islamic Religious Education (PAI) teachers in fostering students' mental health at SMKN 1 Sijunjung. This study uses a qualitative approach with a case study type. The research subjects include BK teachers, PAI teachers, and the school principal who were selected purposively. Data collection techniques were conducted through in-depth interviews, observation, and documentation. The obtained data were analyzed through stages of data reduction, data presentation, and conclusion drawing, and their validity was tested through source and method triangulation techniques. The research results show that the collaboration between the school counselor (BK) teacher and the Islamic education (PAI) teacher at SMKN 1 Sijunjung is carried out through the integration of religious values in counseling services, coordination in handling student issues, as well as character and religious development activities. This collaboration is supported by good communication and cooperation among teachers, although there are still challenges such as time constraints, the absence of a systematic collaboration program, and limited competence in integrating psychological and spiritual approaches. Nevertheless, this collaboration has a positive impact on students' mental health, such as improved ability to manage emotions, inner calm, and more positive behavior.